Produção in vitro de embriões de vacas nelore suplementadas com gordura protegida - Souza, Moacir Rogério de (2012)
This study was carried out with the objective of evaluate the quantity and quality of oocytes, blood parameters, rate of cleavage, rate of embryo production, as well as the rate of pregnancy of transferred embryos from Nellore cows lactating supplemented with rumen-protected fat (Lacto Plus®). For all experiments were used Nellore lactating multiparous cows, kept in paddocks. The Supplements offered were formulated to be isoenergetic and isoproteic. After 14 days of adaptation to supplements, the experimental groups were underwent to an average of 4.93 ± 1.55 and 2.53 ± 1.35 sessions of ovum pick-up, at intervals of 21.71 ± 11.76 and 27.65 ± 21.72 days in experiments 1 and 2, respectively. In the first experiment, a total of 30 Nellore cows were randomly divided into two experimental treatments. Treatment 1 (T1), supplement control (n = 15), without addition of fat. Treatment 2 (T2) supplement with addition of 0.2 Kg/day of rumen-protected fat (n = 15). The oocytes harvest were counted and classified according to their morphology in viable (grade I, II and III) and non-viable (without cumulus, expanded, atretic and degenerated). Blood samples were obtained, in four different periods, for measurement of total cholesterol (TC), high density lipoprotein (HDL-C), low density lipoprotein (LDL-C) and very low density lipoproteins (VLDL-C), triglycerides (TGC), plasma urea nitrogen (PUN) and the hormone insulin. There was no difference (P>0.05) between T1 and T2 regarding number of oocytes harvest, viable and non viable as well as their different morphological classifications. There was no effect (P>0.05) of treatment or interaction treatment with period (P>0.05) in plasma concentrations of VLDL-C and TGC. However, there was effect (P<0.05) of interaction of treatment with period for the concentrations of TC, LDL-C, NUP and insulin and effect of treatment was observed (P<0.05) for HDL-C between T1 and T2. In the second experiment, a total of 15 Nellore cows were randomly divided into two experimental treatments. Treatment 1 (T1), supplement control (n = 6), without addition of fat. Treatment 2 (T2) supplement with addition of 0.2 Kg/day of rumen-protected fat (n = 9). The oocytes harvest were morphologically evaluated, selected, maturated, fertilized and cultivated for embryo production in vitro. The embryos produced were transferred into recipients previously undergone embryo transfer protocol at fixed time. The Pregnancy diagnosis and identification of fetal sex were performed at 53 days after the transfer of embryos. The data analysis did not evidence statistically significant difference (P>0.05) between T1 and T2 regarding number of oocytes harvest (20.90 ± 4.50 vs 25.41 ± 4.42) and the percentage of viable oocytes (89.27 ± 1.83 vs 88, 10 ± 1.33) as well as cleavage rate (70.72 ± 5.56 76.12 ± 3.88 vs), production rate of embryo (51.71 ± 5.22 vs 52.35 ± 3.96) and pregnancy rate (38.38 ± 4.16 vs 39.12 ± 2.89). The results of present study concluded that supplementation with protected fat did not alter the number and morphological quality of oocytes harvest, cleavage rate, production rate of embryo and pregnancy rate. However, alter the concentrations of TC, HDL-C, LDL-C and the hormone insulin.